El género "Debachiella" y la clasificación de los afelínidos (Hymenoptera: chalcidoidea) - De Santis, Luis M. (1979)
In this paper the authors describe Debachiella citri new species from Corrientes, reared from Aonidiella aurantii (Mask.) (Homopt era: Diaspididac). The genus Debachiclla does not fit into the classification of the Aphelinidae as proposed by De Santis (1946) and not fit into the classification of the Aphelinidae as proposed as an anomalous member of the Aphelininae. The new synonymy of Prospaltellinae Nikolskaja et Jasnosli, 1966 with Pteroptricinae Ashmead, 1904 and the new combination Debachiclla brevifuniculat'a (Viggiani, 1972) for Centrodora brevifuniculata, are established.